2017
DOI: 10.1074/mcp.m116.061499
|View full text |Cite
|
Sign up to set email alerts
|

A Luciferase-fragment Complementation Assay to Detect Lipid Droplet-associated Protein-Protein Interactions

Abstract: A critical challenge for all organisms is to carefully control the amount of lipids they store. An important node for this regulation is the protein coat present at the surface of lipid droplets (LDs), the intracellular organelles dedicated to lipid storage. Only limited aspects of this regulation are understood so far. For the probably best characterized case, the regulation of lipolysis in mammals, some of the major protein players have been identified, and it has been established that this process crucially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 74 publications
3
26
0
Order By: Relevance
“…Curiously, the core histones H3 and H4 are similarly overabundant, but present in a different, as yet uncharacterized location. LD localization of histones is mediated by the novel protein Jabba, which likely acts as histone anchor: Jabba physically interacts with these histones, histones are absent from embryonic LDs in Jabba mutants, and the expression of Jabba in cultured Drosophila cells is sufficient to induce recruitment of histones to LDs [156, 157]. …”
Section: Protein Storage – the Case Of Histonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Curiously, the core histones H3 and H4 are similarly overabundant, but present in a different, as yet uncharacterized location. LD localization of histones is mediated by the novel protein Jabba, which likely acts as histone anchor: Jabba physically interacts with these histones, histones are absent from embryonic LDs in Jabba mutants, and the expression of Jabba in cultured Drosophila cells is sufficient to induce recruitment of histones to LDs [156, 157]. …”
Section: Protein Storage – the Case Of Histonesmentioning
confidence: 99%
“…Restriction of both organelles to the same 1D tracks may promote enhanced interactions between them. Clustering of LDs is also frequently observed when certain droplet-localized proteins are up- or downregulated or posttranslationally modified, such as PLIN1 [212, 226], ancient ubiquitous protein 1 (AUP1 [227]), and CG9186 [157, 228]. To what extent such clustering involves altered droplet motility has yet to be examined but, for U2OS cells, it was recently shown that dissociation of clustered droplets involves actin and myosin [229].…”
Section: Other Roles Of Lipid Dropletsmentioning
confidence: 99%
“…The clustering phenotype was dependent on the ubiquitination status of AUP1, since overexpression of a CUE domain mutant that was not ubiquitinated did not induce clustering, but fusion of this mutant to ubiquitin at its C-terminus rescued AUP1-induced clustering [136]. Similarly, ubiquitination of Drosophila LD protein CG9186 in Kc167 cells was required for LD clustering induced by CG9186 overexpression [137,138]. A model that explains the clustering phenotype observed in these studies is that ubiquitinated AUP1 or CG9186 promotes the formation of ubiquitin-dependent homo- or hetero-dimers that bridge adjacent LDs.…”
Section: Connections Between Lds and The Ubiquitin-proteasome Systemmentioning
confidence: 99%
“…Given that LDAPs are involved in multiple aspects of LD biology, and that LD coat proteins are known to function in general as part of highly regulated protein-protein interaction networks in other organisms (Tsai et al, 2015;Kolkhof et al, 2017), we employed Arabidopsis LDAP3 as 'bait' in a yeast two-hybrid (Y2H) assay screen to identify new proteins involved in biogenesis and/or function of plant LDs. We chose LDAP3 as the specific 'bait' since it is the most highly and ubiquitously expressed LDAP gene in Arabidopsis, including in seeds (Gidda et al, 2016).…”
Section: Introductionmentioning
confidence: 99%